Dear Mr.Pavan,I have an inter.ques!

Asked by Nishal | 2nd May, 2008, 01:42: PM

Expert Answer:

x =[ (p+2q) + (p-2q)] / [ (p+2q) - (p-2q)]

x [(p+2q)  - (p-2q)] = [(p+2q) + (p-2q)]

multiply both sides with [(p+2q) + (p-2q)]

x [(p+2q)  - (p-2q)]2 = [(p+2q) + (p-2q)] [(p+2q) - (p-2q)]

x [ p + 2q + p - 2q - 2(p+2q)(p-2q) = (p+2q) - (p-2q)

2px - 2x (p+2q)(p-2q) = p + 2q - p + 2q

2px - 4q = 2x(p+2q)(p-2q)

px - 2q = x(p+2q)(p-2q)

squaring both sides we get

p2x2 + 4q2 - 4pqx = x2 (p2 - 4q2)

p2x2 + 4q2 - 4pqx - p2x2 + 4q2x2 = 0

4q2 - 4pqx + 4q2x2 = 0

q2 - pqx + q2x2 = 0

q - px + qx2 = 0

qx2 -px + q = 0

Answered by  | 3rd Jun, 2008, 05:50: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.